GENESIS AND STAGES OF RENOVATION IN ARCHITECTURE AND URBAN PLANNING OF "NEW CITIES" BASED ON THE EXAMPLE OF AKTAU (SHEVCHENKO) (Advances in Civil and Architectural Engineering, 2021)
This article deals with the problems of cities built during the second half of the 20th century, which in the literature, are referred to as "new." Today, they have changed or have not yet determined the city-forming vector of development, the basis of which was initially, as a rule, large-scale industrial complexes. The search for new ideas and design solutions lies in grounding scientific research and conducting design workshops to create a bank of architectural and town-planning proposals. Based on the example of the city of Shevchenko (now Aktau), a study of its architectural genesis and the phenomenon of the rapid implementation of a project, which received the highest architectural award, namely, the Patrick Abercrombie Prize, the modern strategy of renovation, and development of the city is considered. Positive experience requires study, and it can be applied to “new” cities and partially applied to historically formed cities.